Pierre Bourdieu in Hispanic Literature and Culture (Springer International Publishing, 2018)
Pierre Bourdieu in Hispanic Literature and Culture is a collective reflection on the value of French sociologist Pierre Bourdieu's work for the study of Spanish and Latin American literature and culture. The authors deploy Bourdieu's concepts in the study of Modernismo, avant-garde Mexico, contemporary Puerto Rican literature, Hispanism, Latin American cultural production, and more. Each essay is also a contribution to the study of the politics and economics of culture in Spain and Latin America. The book, as a whole, is in dialogue with recent methodological and theoretical interventions in cultural sociology and Latin American and Iberian studies. .